Chironomidae (Diptera) em córregos de baixa ordem em áreas florestadas do estado de São Paulo, Brasil - Roque, Fábio de Oliveira (Universidade Federal de São Carlos, 2005)
With the aim of understanding the distribution of Chironomidae (Diptera) in Brazilian Atlantic Forest streams at multiple spatial scales, we carried out three complementary studies, which are presented here as chapters: 1) we focus on Chironomidae species richness; 2) we assess the Chironomidae larvae distribution attempting to explore some aspects that could be most influential in determining the chironomid spatial distribution; 3) we report the occurrence of chironomid larvae in fallen-fruits in Atlantic Forest streams. We selected 5 sites in the State of São Paulo and we designed a stratified sampling design incorporating environmental characteristics that potentially may influence chironomid distribution in the different scales (variation among sites streams mesohabitats). We used different sampling methods for collecting larvae, exuviae and adults of Chironomidae. As a whole, our results allow us to point out: 1) low order streams from Atlantic Forest as one of the most chironomid speciose areas in the world; 2) the chironomid assemblage is taxonomically deep, with some genera being represented by a large number of species (Tanytarsus, Caladomyia, Polypedilum, and Stenochironomus); 3) the identification of the scale importance depends on the chironomid assemblage descriptor and the taxonomic resolution considered; 4) studies focusing on one scale or habitat (e.g. riffles) are not appropriate for studying Chironomidae distribution patterns and richness in low order streams; 5) biological traits of some groups may underlie most evident in-stream chironomid distribution pattern; 5) the input of allochthonous matter from riparian vegetation, particularly fallen-fruits, represents an important habitat and food resource for chironomids in Atlantic Forest streams.
Keywords: Ecologia aquática; Insetos aquáticos; Ecologia de comunidades; Macroinvertebrados bentônicos; Mata Atlântica; CIENCIAS BIOLOGICAS::ECOLOGIA